Thermal Coupling Simulation Analysis of Non-smooth Brake Discs with Orthotropic Anisotropic C/SiC - Zhu Yuling; Wang Youqiang; Li Mengjie; Zhao Tao; He Yan (Jixie chuandong)
A simplified three-dimensional brake model with crater structure is established by using the finite element software Abaqus, and the influence of the depth, diameters, degrees and types of craters on the temperature and stress of the brake disc is investigated by combining the thermal coupling theory and the orthogonal test method. On this basis, the temperature and stress fields of brake discs with different non-smooth surface forms are analyzed, and the influence of temperature with radius on non-smooth discs with different braking initial speeds and pressures during emergency braking is investigated under the optimal combination. The results show that the square pit brake disc with the pit depth of 5 mm, the diameter of 8 mm and the 20° interval between adjacent pits in the circumferential direction has the smallest temperature and stress by the orthogonal test method, which is the optimal combination. Among them, the square pit brake disc has the best heat dissipation performance. With the increase of the initial speed and pressure of braking, the temperature of this brake disc surface gradually increases, the highest temperatures of the brake disc all appeares in the brake disc radius of 136 mm.